Impact of the COVID-19 Pandemic on Individuals With Hearing Loss and Audiology Practice in a Developing Country. - Tian Kar Quar; Nor Rashid, Mohd Fadzil; Mohd Rosdi, Muhd Yusran; Wan Syafira Ishak; Foong Yen Chong (American Journal of Audiology, 2023)
Objective: This study aimed to determine the challenges faced by individuals with hearing loss at a time when many nations were attempting to move from the COVID-19 pandemic to endemic. Design: A cross-sectional survey was conducted on Malaysian adults with hearing loss to determine the impact of the COVID-19 crisis on hearing aid management, communication difficulties, psychosocial challenges, and access to audiological services. Study Sample: One hundred forty-six individuals aged 18 years old and above with hearing loss were recruited from hearing health care centers to participate in the survey. Results: Many of the participants (54.2%) reported significant difficulties communicating with people wearing face masks. For hearing aid management, repairing (36.3%) and fine-tuning devices (30.2%) were considered more challenging than obtaining a battery (21.3%). The COVID-19 pandemic had a serious psychosocial impact on a small portion of the individuals surveyed. Remote services were rarely offered by the audiologists, and most participants preferred in-person treatment. However, the majority perceived that creating awareness and training on telehealth was important. Conclusions: Effective management for people with hearing loss needs to consider the challenges faced by them, as the world prepares to live with the coronavirus. Clinical protocols should consider providing a service that is helpful for the clients as well as safe and sustainable in future pandemics.